Mechanical And Thermal Properties Of Renewable Oil Palm Shell Lightweight Concrete Reinforced With Synthetic Polypropylene Fibres - Loh, Leong Tatt (2021)
Being the second largest exporter of palm oil globally, Malaysia generated approximately 6.3 million tonnes of oil palm shell (OPS) in 2018. OPS are solid waste products from the palm oil mill. Researches of using OPS as aggregates in concrete have been initiated as the specific gravity of the shells is 1.1 – 1.4 g/cm3, which falls within the range of lightweight aggregates. Previous studies show that the mechanical performance of oil palm shell lightweight concrete is lower than other types of lightweight aggregate concrete. Therefore, synthetic polypropylene fibres are added to enhance the mechanical properties, especially in splitting tensile strength and modulus of rupture. The effects of two different types of synthetic polypropylene fibres on the mechanical and thermal properties of OPS concrete are investigated in this research. The fibres are singly and hybrid reinforced in different volume fractions (0.1%, 0.3% and 0.4%). The oven-dried density of the OPS concrete produced is between 1936.7 kg/m3 to 1976.5 kg/m3 with compressive strength of more than 25 MPa at 28-days. A new mixing method has been proposed, which shows significant improvement in workability and compressive strength. The research outcome has proven that the inclusion of fibres is more prominent in improving the residual strength properties of OPS concrete. The research finding has proven that the bridging effect of fibres modifies the failure modes of OPS concrete. In addition, synthetic polymer fibres of small diameter increase the thermal conductivity; while synthetic polymer fibres of large diameter decrease the thermal conductivity. Hence, the findings of this study prove that synthetic polypropylene fibres can be used to enhance the mechanical and thermal properties of OPS lightweight concrete.